1980
DOI: 10.1210/endo-106-5-1634
|View full text |Cite
|
Sign up to set email alerts
|

Differential Response of Individual Uterine Cell Types from Immature Rats Treated with Estradiol*

Abstract: The separation of viable epithelial, stromal, and myometrial cells from immature rat uteri is described. The integrity of the separated cells was established by their ability to grow in culture and to exclude trypan blue and by transmission and scanning microscopy. Epithelial preparations contain insignificant contamination by other cells. Stromal fractions are estimated to contain 10% epithelial contamination. Myometrial fractions probably contain significant contamination by stroma, but the amount is difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
67
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(68 citation statements)
references
References 54 publications
1
67
0
Order By: Relevance
“…However, such patterns in prenatal rodents are not well understood. Similarly, 17 -estradiol effects on reproductive tract cell proliferation have been well reported in immature and adult rodents (McCormack & Glasser 1980, Quarmby & Korach 1984. However, -fetoprotein limits fetal 17 -estradiol exposure in utero.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, such patterns in prenatal rodents are not well understood. Similarly, 17 -estradiol effects on reproductive tract cell proliferation have been well reported in immature and adult rodents (McCormack & Glasser 1980, Quarmby & Korach 1984. However, -fetoprotein limits fetal 17 -estradiol exposure in utero.…”
Section: Introductionmentioning
confidence: 84%
“…EGF and insulin-like growth factor (IGF)-I stimulate cell proliferation in immature mouse uterine and vaginal epithelial cells in vitro (Tomooka et al 1986, Iguchi et al 1987, Shiraga et al 1997. Because estrogen stimulates uterine epithelial cell proliferation (McCormack & Glasser 1980, Quarmby & Korach 1984 and expression of EGF, IGF-I, heparin-binding EGF-like growth factor, transforming growth factor (TGF)-and EGF-R in the reproductive tracts of mice and rats, these growth factors may mediate the estrogen-induced proliferative and differentiative responses in rodent reproductive tracts (Murphy et al 1987, DiAugustine et al 1988, Nelson et al 1991, Beck & Garner 1992, Ignar-Trowbridge et al 1992, Kapur et al 1992, Das et al 1994, Sahlin et al 1994, Zhang et al 1994, Falck & Forsberg 1996, Hom et al 1998. In the fetal reproductive tract, expression of EGF-R in mice (Bossert et al 1990), and EGF, TGFand IGF-I in rats (Koike & Noumura 1993, Kanno et al 1994, Gu et al 1999) was reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that oestrogen administration caused the induction of its own receptor. This phenomenon has not been widely recognized in humans, although oestrogen-stimulated induction of its own receptor has been reported in several animal models (McCormach and Glasser, 1980;Sutherland et al, 1980;Lessey et al, 1981). Piva et al (1988) have demonstrated an increase in ER mRNA in human breast cancer cell lines cultured with oestradiol.…”
Section: Discussionmentioning
confidence: 99%
“…The endometrium, located in the inner part of the organ, is the site of blastocyst implantation, and its epithelium undergoes cyclic radical changes under the control of ovarian sex steroid hormones (1); estrogens are responsible for epithelial cell hyperplasia, whereas progesterone blocks cell proliferation and induces differentiation. The myometrium (2), in the outer part of the uterus, accounts for more than 60% of the whole organ (3) and has a primordial role in uterine function. Whereas muscle quiescence due to high progesterone levels is essential during most of the pregnancy (4), efficient myometrium contractility is fundamental for a normal labor (for a review, see Ref.…”
mentioning
confidence: 99%